Tonsils as an in vivo model : Virus infections, microbiome, and immune responses - Ivaska, Lotta (fi=Turun yliopisto|en=University of Turku|, 2022)
Tonsillectomy and adenotomy are two of the most common operations in the otorhinolaryngology field. Recurrent infections and hypertrophy are the main indications for these surgical procedures. Palatine tonsils and nasopharyngeal tonsil (adenoid) continuously interact with our environment. Tonsils consist of mucosa associated lymphoid tissue and serve as a site for bacteria, viruses, and other antigens to be presented to the immune cells. Physiologically complex tonsil tissue is crucial in inducing and maintaining immune responses. However, the underlying mechanisms of the pathological conditions are not fully understood. This thesis primarily aimed to investigate tonsillar virus infections, microbiome, and their association with immune responses. The diagnostics and immunomodulatory effects of human bocavirus 1 (HBoV1) were particularly emphasised. Elective adeno-/tonsillectomy patients of all ages were recruited from Satakunta Central Hospital 2008–2009 and Turku University Hospital 2013–2015. Adeno-/tonsillectomy was performed according to routine clinical procedures; tonsil tissues, nasopharyngeal aspirate (NPA), and serum samples were collected. Virus diagnostics was done by polymerase chain reaction (PCR); the expression of cytokine and transcription factors was analysed by reverse-transcription PCR. RNA sequencing was used for microbial profiling. Our results support earlier data that respiratory virus infections in palatine tonsil tissue, adenoid tissue, and NPA are common (with a total detection rate of 94%) in non-acutely ill adeno-/tonsillectomy patients. Additionally, in one or more of the sample sites, human herpesviruses 6 and 7 and the Epstein-Barr virus were commonly found (67%, 51%, and 35%, respectively). High HBoV1 DNA loads in NPA had no correlation with serology or messenger RNA results. Furthermore, HBoV1 infection was associated with suppressed expression of tonsillar cytokines, suggesting the immunosuppressive capacity of the virus. Our study revealed that atopy associated with lower intratonsillar bacterial diversity, suggesting differences in microbial balance between atopic and non-atopic subjects. Palatine tonsil and adenoid tissues serve as an in vivo model to investigate viruses, bacteria, and their interactions with local immune responses.

Risakudos in vivo -mallina – virusinfektiot, mikrobiomi ja immuunivasteet Nielurisa- ja kitarisaleikkaus ovat yleisiä toimenpiteitä korva-, nenä- ja kurkkutautien alalla. Leikkausindikaatio on useimmiten risatulehdukset ja risojen liikakasvu. Nielu- ja kitarisat ovat jatkuvasti vuorovaikutuksessa ympäristön kanssa. Risakudos koostuu limakalvon ja lymfaattisen kudoksen yhdistelmästä ja toimii antigeenin ja immuunijärjestelmän solujen kohtaamispaikkana. Fysiologisesti monimuotoinen risakudos toimii merkittävässä roolissa immuunivasteiden aktivoinnissa ja muokkaamisessa. Tämän väitöskirjan tarkoituksena oli tutkia risakudoksen virusinfektioita, mikrobiomia ja niiden yhteyttä immuunivasteisiin. Erityisesti tutkittiin bokaviruksen (HBoV1) diagnostiikkaa ja HBoV1 infektion yhteyttä immuunivasteisiin.Aineistoon kerättiin kaiken ikäisiä kita- ja nielurisaleikkauspotilaita Satakunnan keskussairaalasta vuosina 2008–2009 ja Turun Yliopistollisesta keskussairaalasta vuosina 2013–2015. Leikkauspotilaista otettiin verinäytteet, nenän imulimanäytteet (NPA) ja risakudosnäytteet. Virukset analysoitiin polymeraasiketjureaktio (PCR) menetelmällä. Sytokiinigeenien ilmentymistä tutkittiin käänteistranskriptaasipolymeraariketjureaktiolla (RT-PCR) ja RNA-sekvensointia käytettiin risakudoksen mikrobiomin kartoittamiseen. Kroonista risasairautta sairastavien leikkauspotilaiden risakudoksissa ja nenän imulimassa esiintyy runsaasti hengitystieviruksia (esiintyvyys 94 %), kuten aikaisemmin on osoitettu. Herpesvirus 6 (HHV6), herpesvirus 7 (HHV7) Epstein-Barr virus olivat yleisiä (67 %, 51 %, 35 %) yhdessä tai useammassa näytelaadussa. HBoV1 korkea virusmäärä ei korreloinut vasta-ainetasoihin tai lähetti RNA tuloksiin. HBoV1 oli yhteydessä risakudoksen sytokiinigeenien vähäisempään ilmaantuvuuteen viitaten HBoV1:n kapasiteettiin muokata immuunivastetta. Lisäksi tutkimuksessa kävi ilmi, että atooppisilla potilailla nielurisakudoksen bakteerien monimuotoisuus on alhaisempi. Nielu- ja kitarisa soveltuvat käytettäväksi in vivo mallina tutkittaessa risakudoksen viruksia, bakteereja ja niiden vaikutusta immuunivasteisiin.